“ANALISIS AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA (ADD) DALAM UPAYA MENINGKATKAN PEMBANGUNAN DAN PEMBERDAYAAN MASYARAKAT DI DESA TELAGA TAWANG, KECAMATAN SIDEMEN, KABUPATEN KARANGASEM TAHUN 2019 - Dewi, Komang Tri Utari; Wirantari, I Dewa Ayu Putri; Yasintha, Putu Nomy (CITIZEN CHARTER; Vol 2 No 2 (2022): Administrasi Publik 2022, 2023)
In an effort to enhance community development and empowerment in Telaga Tawang village, the purpose of this study is to ascertain how the management of village money distribution is held accountable. The implementation of Law Number 6 of 2014 Concerning Villages gave rise to the Village Fund Allocation Management program, which aims to enhance one component of good governance and has accountability as one of its foundations. The government's effort to improve government administration is called accountability. It takes the form of rural communities' development and empowerment and is based on good governance. The type of research that was done used a descriptive qualitative research approach. Instruments for interviews, observations, and documentation are used in data gathering approaches. The principle of accountability put out by Jay M. Shafritz and E.W. Russell demonstrates planning, execution, management, and accountability indicators. The findings demonstrated that, in terms of planning, execution, administration, and accountability indicators, the management of village fund allocation (ADD) has been operating successfully. Participation of the community in planning the distribution of village money, however, is still a problem. The management of village fund allocations has been running smoothly, and the transparency provided by the village government has been good with the realization in accordance with the village fund allocation planning, with the construction of residential roads being one example. This is based on the development and empowerment of village communities. Keywords: accountability, Village Fund Allocation, development and empowerment